The genus Fissidens (Fissidentaceae) from Brazilian Oceanic Islands: Trindade Island and Martin Vaz Archipelago - Alkimim-Faria, Allan Laid; Teixeira, Tamara Poliana De Oliveira; Bordin, Juçara; Carvalho-Silva, Micheline (Phytotaxa, 2025)
The Trindade Island is located in the South Atlantic, about 1,200 km from the Brazilian coast. Although is a small island, area totaling 9.28 km², Trindade hosted high number of endemic species, including 15 endemic plants. The flora is compost mainly by angiosperms, but 32 species of bryophytes, distributes in three botany divisions, live in the island. Fissidentaceae is the second largest family of mosses from Brazil, with 72 species distributed in all Brazilian biomes, and two species were recognized to Trindade Island. Studies with Fissidentaceae from Brazil, made is possible to recognize a new species of Fissidens from Trindade Island and a new occurrence of Fissidens was found in the Martin Vaz Archipelago. Here we propose the new species, Fissidens trindadensis, the name was used in a previous publication, but as an invalid name according the International Code of Nomenclature for algae, fungi, and plants. Now the taxa are here described, illustrated and compared with morphologically similar species.